Program Bimbingan dan Konseling dalam Tinjauan Perilaku Perundungan untuk Siswa SD di Pangkalpinang - Hevitria; Said Akhmad Maulana; Muhamad Tohir (CENDEKIAWAN, 2026)
Recently, the phenomenon of bullying in schools has become a serious concern due to its profound impact on victims. This is due to the lack of optimal guidance and counseling programs for students in schools. Bullying is repeated, psychologically or physically, oppression perpetrated by an individual or group of individuals who are superior to them. Bullying cases are common, especially in education, and if left untreated, can have negative impacts on victims. This study was conducted to understand the guidance and counseling programs implemented by guidance and counseling teachers in handling and developing the character of students involved in bullying in elementary schools in Pangkalpinang City. This research employed a qualitative method with a focus on case studies, which involved collecting interviews, observations, and document analysis from various previous studies. The data used consisted of primary and secondary sources. The primary source was questionnaires, while secondary sources included books on interpersonal models for preventing bullying. The results of the study indicate that the literature review method revealed that anti-bullying awareness among students can be increased through several methods, including: guidance groups using sociodrama techniques, psychosocial education, and information delivery using animated media. Furthermore, collaboration between all parties, particularly schools, teachers, students, and parents, is essential in creating a more positive environment for students. School counselors play a crucial role in preventing and addressing bullying issues in the school environment.